Capacity development in the Humidtropics research program - International Livestock Research Institute (CGIAR Research Program on Integrated Systems for the Humid Tropics, 2017)
This film describes the role of capacity development in accelerating adoption of new technologies and innovations in the CGIAR Research Program on Integrated Systems for the Humid Tropics.